BLADDER RECONSTRUCTION DURING SEPARATION OF A CONJOINT TWIN ISCHIOPAGUS TRIPUS - Effendi, Fajar; Siregar, Safendra; Sibarani, Jupiter (Indonesian Journal of Urology, 2019)
Objective: Conjoined twins represent one of the rarest congenital anomalies occurring with a varying incidence of about approximately 1 : 50.000 - 1 : 200.000 births. Ischiopagus conjoined  twinning (Fuse at the hip region) is even rare representing only 6% of all conjoined  twins. Here we report our experience in lower urinary tract reconstruction during separation of a conjoined twin ischiopagus tripus in Hasan Sadikin Hospital, Bandung. Case(s) Presentation: Two years old female conjoined twins, weighing in total of 8 kilograms, were brought to our hospital. The twins were fused  at  the lower  halves of  their bodies with two separate lower limbs at the right side and a fused left lower limb. External genitalia were absent. From CT Angiography we found four kidneys, two in each child with two separate bladders, with right ureter of baby A and left ureter of  baby B enter the  right bladder, while left ureter of  baby A and  right ureter of  baby B enter the left bladder. There was one cloaca that drains urine and feces. During the separation surgery, we performed ureteroneocystostomy and temporary ureteral stenting, followed by cystostomy. The pediatric surgeon performed bowel separation by stapling technique, pelvic wall separation, ileostomy, and pelvic floor reconstruction. The orthopedic surgeon performed femur separation, pelvic floor reconstruction, reconstruction of the pelvic ring, and femur reconstruction. The patients underwent defect closure, which performed by plastic surgeon. The operation was successful, without any complication to the kidney and the urinary tract of both babies. Discussion: Ischiopagus conjoined twins are the most complex conjoined twins and occur in only 6% of all conjoined twin cases. Ischiopagus is usually located along the axis with the head located on the opposite side. This case usually has one umbilicus and the two bodies are fused below this level, the union occurs in the lower abdomen and the pelvis. The internal organs that usually coalesce in cases of ischiopagus conjoined twins are liver, lower gastrointestinal, and genitourinary. The fused gastrointestinal part is the ileo-colic part of terminal ileum (Meckel's diverticulum). Conclusion: The separation of conjoined twin is a unique challenge due to its complex anatomy and physiology. Although advancement in imaging and monitoring has improved the survival rate separation can be successfully achieved only with meticulous planning and team work.